Co-processing of bio-oil from de-oiled Jatropha curcas seed cake with refinery gas–oil over sulfided CoMoP/Al2O3 catalyst. Issue 114 (5th December 2016) - Poddar, Mukesh Kumar; Rai, Aditya; Maurya, Mannar Ram; Sinha, Anil Kumar
Abstract : Schematic representation of Co-processing of bio-oil from de-oiled Jatropha curcas seed cake with refinery gas–oil over sulfided CoMoP/Al2 O3 catalyst. Abstract : A sulfided cobalt–molybdenum–phosphorus/aluminium oxide (CoMoP/Al2 O3 ) catalyst was studied in the hydroprocessing of bio-oil (BO) obtained from the pyrolysis of de-oiled Jatropha curcas seed cake. Hydroprocessing was carried out with different ratios of refinery gas oil (GO) and BO. The oxygen content in the products was reduced to trace amounts after hydroprocessing. A clear product obtained from the co-processing of BO with refinery GO contained 2–16% gasoline, 30–35% kerosene, 35–44% diesel, with 50–60% alkanes, 10–45% cycloalkanes, and 1–10% aromatics, with a negligible amount of char formed in the process. Hydroprocessing of 100% BO produced 30% kerosene and 30% diesel, together with 10% gasoline, with 15% of alkanes and 15% cycloalkanes, and 45% aromatics. A maximum amount of kerosene (41%) was obtained at 648 K and 75 bar from 100% BO, with a small amount of char (1.5%) deposited on the catalyst. In comparison, over sulfided CoMo/Al2 O3 catalyst (without P promoter) only 31% of kerosene was produced, with 17% char, using similar reaction conditions.